2018
DOI: 10.1038/s41419-018-1234-1
|View full text |Cite
|
Sign up to set email alerts
|

CCN3 and DLL1 co-regulate osteogenic differentiation of mouse embryonic fibroblasts in a Hey1-dependent manner

Abstract: Notch signaling pathway is one of the most important pathways to regulate intercellular signal transduction and is crucial in the regulation of bone regeneration. Nephroblastoma overexpressed (NOV or CCN3) serves as a non-canonical secreted ligand of Notch signaling pathway and its role in the process of osteogenic differentiation of mesenchymal stem cells (MSCs) was undefined. Here we conducted a comprehensive study on this issue. In vivo and in vitro studies have shown that CCN3 significantly inhibited the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…In a recent study, we reported that BMP9 (also termed as growth differentiation factor 2) is one of the most potent BMPs among the 14 types of BMPs in the induction of osteogenic differentiation 19,56 . BMP9 usually produces its marked effect through the BMP/Smad signaling pathway, which includes the canonical BMP/Smad pathway or the non-canonical BMP/ Smad pathways, such as ERK and p38 MAPK pathway 57 . In the canonical BMP/Smad pathway, BMP9 activates the corresponding phosphorylated R-Smad (named Smad1/5/ 8), and the phosphorylated Smad1/5/8 (p-Smad1/5/8) recruits and phosphorylates Smad4 to form the complex.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we reported that BMP9 (also termed as growth differentiation factor 2) is one of the most potent BMPs among the 14 types of BMPs in the induction of osteogenic differentiation 19,56 . BMP9 usually produces its marked effect through the BMP/Smad signaling pathway, which includes the canonical BMP/Smad pathway or the non-canonical BMP/ Smad pathways, such as ERK and p38 MAPK pathway 57 . In the canonical BMP/Smad pathway, BMP9 activates the corresponding phosphorylated R-Smad (named Smad1/5/ 8), and the phosphorylated Smad1/5/8 (p-Smad1/5/8) recruits and phosphorylates Smad4 to form the complex.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that BMP9 is in possession of the regulatory function of vascularization in MSCs and endothelial cells. BMP9 works its function through BMP/Smad signaling, including p38-MAPK and ERK1/2-MAPK pathway [ 50 52 ]. For the canonical BMP signaling pathway, which activates the R-Smad named phosphorylated Smad1/5/8 (p-Smad1/5/8) through binding with its membrane receptor, and then forming a complex with the phosphorylated Smad 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of CCN3 on osteogenesis are particularly controversial. Several reports indicated osteogenic potential, whereas others showed inhibitory effects [ 82 , 83 , 84 ], clearly representing the context dependence of the CCN-induced biological outcomes. The osteogenic effects observed in certain studies might be caused via CCN2- or CCN3-specific molecular partners that were present in the microenvironment under the experimental conditions employed therein.…”
Section: Molecular Interaction Between Ccn2 and Ccn3mentioning
confidence: 99%